The Sjögren's syndrome-associated autoantigen Ro52/TRIM21 modulates follicular B cell homeostasis and immunoglobulin production. (16th October 2018) - Brauner, S; Ivanchenko, M; Thorlacius, G E; Ambrosi, A; Wahren-Herlenius, M
Summary: Systemic rheumatic diseases are characterized by abnormal B cell activation with autoantibody production and hypergammaglobulinaemia. Ro52/SSA, also denoted tripartite motif (TRIM)21, is a major autoantigen in Sjögren's syndrome and systemic lupus erythematosus. Interestingly, TRIM21-deficient mice develop systemic autoimmunity with B cell-driven manifestations such as autoantibodies, hypergammaglobulinaemia and glomerulonephritis following tissue injury. The mechanisms by which TRIM21-deficiency leads to enhanced B cell activation and antibody production are, however, not well understood, and to further elucidate the role of TRIM21 in systemic autoimmunity, we investigated the B cell phenotype and antibody responses of Trim21 −/− mice following immunization with thymus-dependent (TD) and thymus-independent (TI) antigens. We found that TRIM21-deficient mice developed significantly higher specific antibody titres than their wild-type counterparts upon B cell receptor (BCR) engagement by TD and TI type II antigens, and this was accompanied by an altered B cell phenotype. Furthermore, BCR cross-linking, but not anti-CD40 stimulation, in vitro resulted in a significantly higher proliferation of Trim21 −/− cells. We also observed that splenic follicular B cells were expanded not only in immunized mice but also already in young, unmanipulated Trim21 −/− mice, and transcriptomic analysis of these cells revealed an up-regulation of genes associated with B cell differentiation, indicating a role for TRIM21 in their regulation. In conclusion, in this study we describe a link between the rheumatic autoantigen Ro52/TRIM21 and increased antibody production associated with follicular B cell expansion, implicating a potential role for Ro52/TRIM21 in the pathogenesis of systemic autoimmune diseases. Graphical Abstract: